The Darwin Agreement: A collaboration between Australian restoration organisations in support of the UN Decade on Ecosystem Restoration. (30th September 2021) - Armitage, Chris; Auld, Tony; Bradby, Keith; Campbell, Heather; Clarkson, Bruce; Cox, Andrew; Dixon, Peter; Fitzsimons, James; Foran, Brendan; Howling, Gary; McLeod, Ian; Norrish, Shane; et al.
Summary: The Darwin Agreement is a collective response from Australian national restoration organisations to the United Nation's declaration of 2021–2030 as the UN Decade on Ecosystem Restoration. The agreement functions as terms of reference for a new alliance, the Restoration Decade Alliance, to optimise on‐ground actions and advocacy to retain native ecosystems, reduce impacts upon them and restore them to the highest extent practicable. The Restoration Decade Alliance is expected to grow in membership and influence throughout the Decade and to help galvanise increased action and improved policy across the whole of Australian society including government, industry and community sectors. The UN Decade initiative seeks to reinforce efforts of all players, small and large, to help shift the currently destructive trajectory of humankind to a trajectory of recovery for the benefit of humans and nature.